НОВАЯ НАХОДКА ГОЛЬЦА СЕВЕРЦОВА NEMACHILUS SEWERZOWII В БАССЕЙНЕ ОЗ.БАЛКАШ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The first time Severtzov’s stone loach (Nemacheilus sewerzowii G.Nikolsky, 1938) has been found in the Sarkand rivulet. This find showed to the large spread of Severtzov’s stone loach in the Balkhash Lake basin at the foremr time. Nowadays the species distribution area consists from a few separeted populations. Biological and morphological features of Severtzov’s stone loach from the Sarkand rivulet were presented in comparison with former data. Description of morphology of digestive system was given. Environmental condition in the Sarkand rivulet was evaluated as quite faborable for Severtzov’s stone loach.